PENGARUH KETERAMPILAN SOFT SKILL DAN KEPUTUSAN KARIR TERHADAP KESIAPAN KERJA DI KALANGAN MAHASISWA STIE WIDYA WIWAHA - Pamella, Pancaly Noveto; Zuraida, Lukia (Program Studi Manajemen Fakultas Ekonomi UST, 2025)
This study aims to determine the effect of soft skills and career decision on work readiness among STIE Widya Wiwaha students. The population used in this study is the Widya Wiwaha student with the total sample of 76 respondents. Data collection is done by spreading the questionnaire online using google form. This type of research used quantitative research. Data processing techniques using IBM SPSS version 22.0 application. The results of this study in indicate that the soft skills amd career decisions are persiling positive and significant effects on work readiness among STIE Widya Wiwaha students. Soft skills and career decisions simultaneously influence positive and significantly to work readiness among STIE Widya Wiwaha students.